Attenuated IGF-1 predicts all-cause and cardiovascular mortality in a Black population: A five-year prospective study. (November 2016) - Schutte, Aletta E; Conti, Elena; Mels, Catharina MC; Smith, Wayne; Kruger, Ruan; Botha, Shani; Gnessi, Lucio; Volpe, Massimo; Huisman, Hugo W
Background: Inconsistent findings are reported on whether insulin-like growth factor-1 (IGF-1) is protective or harmful in predicting hypertension, carotid wall thickness and mortality. We determined the five-year prognostic value of IGF-1 for these outcomes in a large Black population prone to hypertension and cardiovascular disease. Design: A longitudinal study as part of the PURE (Prospective Urban and Rural Epidemiology) study, North West Province, South Africa. Methods: We measured IGF-1 and IGF binding protein-3 (IGFBP-3) in 1038 HIV-uninfected participants (age range 32–94 years) and assessed blood pressure, carotid intima-media thickness and mortality. Results: Over five years 116 deaths occurred. Baseline IGF-1 was similar in survivors and non-survivors ( p  = 0.50), but tended to be higher in survivors upon adjustment for IGFBP-3 and covariates ( p  = 0.061). Normotensives and hypertensives ( p  = 0.072), and those with carotid intima-media thickness < 0.9 mm and ≥ 0.9 mm also displayed similar baseline IGF-1 ( p  = 0.55). Multivariable-adjusted Cox-regression indicated high IGF-1 predicting lower risk for all-cause mortality (hazard ratio 0.45; 0.23–0.88) and cardiovascular mortality (hazard ratio 0.26; 0.08–0.83) when also adjusting for IGFBP-3. When including normo- and hypertensives at baseline, high IGF-1 was related to normotension at follow-up (hazard ratio 0.68; 0.49–0.95). We found no association with carotid intima-media thickness (hazard ratio 0.59; 0.31–1.14). Conclusion: In a Black South African population with low socio-economic status and harmful health behaviours, we found a protective independent association between IGF-1 and hypertension, cardiovascular and all-cause mortality, with no association with carotid wall thickness.